THE BULLYING PHENOMENON AMONG ELEMENTARY SCHOOL STUDENTS: A SYSTEMATIC REVIEW FROM A DEVELOPMENTAL PSYCHOLOGY PERSPECTIVE - Asriana Harahap; Abdul Munip; Samsuddin Pulungan (Waniambey: Journal of Islamic Education, 2025)
Bullying in elementary schools is a critical issue within the context of global education, as it directly impacts children's social, emotional, and cognitive development. This study conducts a Systematic Literature Review (SLR) of Scopus-indexed scientific publications from 2014 to 2024 to identify developmental factors associated with bullying in children aged 6–12, the most frequently reported forms of bullying, the resulting psychological impacts, and intervention approaches deemed effective. The review process adhered to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol, utilizing data retrieval via Scopus with keyword combinations related to bullying, elementary school, developmental psychology, and peer relations. Out of 31,494 articles identified in the initial phase, only 32 satisfied all inclusion criteria. The main findings indicate that emotional regulation, empathy, peer group dynamics, and the quality of the school climate are the developmental dimensions most influential in the emergence of bullying behavior. Bullying in elementary schools manifests in various forms, involving physical, verbal, and social aggression, as well as cyberbullying and emotional bullying aimed at harming or dominating other students. The effects of bullying are evident in decreased self-esteem, anxiety, depression, social withdrawal, and disrupted social identity formation. This study underscores the necessity of development-based interventions, such as Social Emotional Learning, strengthening the role of teachers, and implementing school-based prevention programs. Furthermore, the findings reveal that physical, verbal, social, and emotional bullying are the most prevalent forms among elementary school children, whereas cyberbullying is less prevalent due to the lower usage of digital devices among this age group. The authors provide theoretical foundations and practical implications for strengthening anti-bullying policies in elementary schools, including Islamic educational institutions.